2018
DOI: 10.1002/cssc.201800186
|View full text |Cite
|
Sign up to set email alerts
|

A Low‐Energy‐Gap Thienochrysenocarbazole Dye for Highly Efficient Mesoscopic Titania Solar Cells: Understanding the Excited State and Charge Carrier Dynamics

Abstract: Maintaining both a high external quantum efficiency and a large open-circuit photovoltage of dye-sensitized solar cells (DSSCs) is a crucial challenge in the process of developing narrow-energy-gap dyes for the capture of infrared solar photons. Herein, we report two donor-acceptor organic dyes, C294 and C295, with a polycyclic heteroaromatic unit, 6,11-dihydrothieno[3',2':8,9]chryseno[10,11,12,1-bcdefg]carbazole (TCC), as the central module of the electron donor, and ethylbenzothiadiazole-benzioc acid as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…In their further research on donor–acceptor organic dyes, Wang and co-workers reported two more molecules with a NAP-based unit as the central module of the electron donor and ethynylbenzothiadiazole-benzoic acid as the electron acceptor, C5.2a and C5.2b , along with the previously reported model dye C5.1 (Chart ). The thiophene-fused compounds C5.2a and C5.2b were more electron rich, corresponding to a higher HOMO energy and decreased HOMO–LUMO gap compared to C5.1 .…”
Section: Perylenoidsmentioning
confidence: 99%
“…In their further research on donor–acceptor organic dyes, Wang and co-workers reported two more molecules with a NAP-based unit as the central module of the electron donor and ethynylbenzothiadiazole-benzoic acid as the electron acceptor, C5.2a and C5.2b , along with the previously reported model dye C5.1 (Chart ). The thiophene-fused compounds C5.2a and C5.2b were more electron rich, corresponding to a higher HOMO energy and decreased HOMO–LUMO gap compared to C5.1 .…”
Section: Perylenoidsmentioning
confidence: 99%
“…They assumed that the additional side chains in C295 can lead to a more compact and well-arranged molecular layer on the surface of the titania film, which hindered the recombination between electrons in titania and the oxidized species in the electrolyte and accounted for its higher V oc . 8 Zhang et al showed that when the hexyl group was replaced with the dodecyl group as shown in Fig. 1, the V oc increased from 1170 mV to 1240 mV.…”
Section: Introductionmentioning
confidence: 99%
“…Further improving the PCE of DSSCs requires design and synthesis of new high-efficiency organic dyes, which play a pivotal role in absorbing visible light and generating photocurrent. [9][10][11][12][13][14][15] However, the chemical space of possible organic dyes is extremely huge due to the vast number of functional groups and their various linkage combinations, and accordingly, the tedious and expensive trial-and-error experimental procedure becomes the bottleneck to find an optimal dye molecule from such a huge chemical space.…”
Section: Introductionmentioning
confidence: 99%